(untitled) - Karier, Thomas (Armonk, N.Y., 1993)
An introduction to corporate power; the history of monopoly theory; the microeconomics of power; early statistical evidence;....
Keywords: Hợp nhất, sáp nhập các tập đoàn,Consolidation and merger of corporations